Retrocardiac Pneumomediastinum: Description of an Unusual Case and Review of Literature - Federica Porcaro; Alessandro Onofri; Annalisa Allegorico; Paolo Tomà; Renato Cutrera (MDPI AG, 2023)
Retrocardiac pneumomediastinum (RP) is the consequence of air trapping in the inferior and posterior mediastinum. It is characterized by the presence of a right or left para-sagittal infrahilar oval or pyramidal air collection on a chest X-ray. It is usually detected in neonates because of alveolar rupture after invasive ventilation or invasive manoeuvres applied on airways or the digestive tract. A healthy child came to the emergency department (ED) for acute respiratory failure due to viral bronchiolitis when he was 2 months old. Because of his clinical condition, he underwent helmet continuous positive airway pressure (HCPAP). When the condition allowed, he was discharged and sent home. He was re-admitted into the hospital for asthmatic bronchitis 3 months later. A frontal chest X-ray taken during the second hospitalization showed an oval-shaped retrocardiac air lucency not previously detected. Differential diagnosis including digestive and lung malformations was made. Finally, the diagnosis of RP was made. We report an unusual case of retrocardiac pneumomediastinum in a 5-month-old male infant after the application of continuous positive pressure via a helmet. RP presentation after the administration of non-invasive ventilatory support beyond the neonatal age is unusual. Although surgical drainage is curative, conservative treatment can be considered in hemodynamically stable patients.